Effect of step-down temperature drying on energy consumption and product quality of walnuts. (November 2020) - Chen, Chang; Venkitasamy, Chandrasekar; Zhang, Weipeng; Deng, Lizhen; Meng, Xiangyong; Pan, Zhongli
Abstract: The objective of this study was to investigate the effect of step-down temperature drying on the energy consumption and product quality of walnuts in a column dryer. Hot air drying experiments were conducted under constant and stepwise decrease temperature conditions (43, 55, 65 and 75 °C) at fixed air velocity (0.7 m/s). Energy and exergy analyses were performed to determine the energy utilization ratio and the exergy efficiency during the drying process. The results indicated that step-down temperature drying effectively reduced the drying time by up to 40% and energy consumption by 24% while obtaining similar walnut quality and shelf life based on the kernel lightness and oil quality. The findings from this study provide important information in the understanding of walnut drying characteristics and have important practical values for the development of efficient and energy-saving drying methods in the industry. Highlights: Testing of new walnut drying method with step-down temperature hot air. Energy and exergy analyses of walnut drying were performed in a column dryer. Up to 40% drying time reduction and 24% energy saving could be achieved. Improved color, oil qualities and shelf life were obtained in the dried walnuts.